The Handbook of Architectural Practice - The American Institute Of Architects (1953)
Registration of Architects, The Architect and the Owner, The Office, Surveys and Preliminary Studies and Estimates and Working Drawings and Specifications, The Letting of Contracts, The Execution of the Work, The Architect and the Law, Office Records of Completed Work.